2020
DOI: 10.24912/jbmi.v3i1.8036
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Kadar Hidrasi Kulit Dan Kejadian Dermatitis Kontak Iritan Pada Petugas Kebersihan Di Universitas Tarumanagara

Abstract: Irritant contact dermatitis (DKI) is a non-immunologic skin inflammation reaction caused by contact with irritants. A janitor is a worker who does a lot of wet work that will repeatedly contact with irritants such as acids, bases, detergents, soap, water, solvents, etc., so that there will be damage to the skin barrier function that starts with loss of the lipid layer and Natural Moisturizing Factor (NMF) so it will reduce skin hydration levels and increase TransEpidermal Water Loss (TEWL). This makes the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The result of this study indicates that there is a significant relationship between the habit of washing hands and the level of skin hydration in the community in the Banyumas Regency area. The result of this study is supported by research conducted by Chairunnisa et al, (2020) which states that frequent exposure to soap and water can cause damage to the stratum corneum which can increase TEWL and decrease skin hydration-levels. 6, the result of the chi-square analysis shows that the p value between the habit of washing hands and the incidence of irritant contact dermatitis is 0.394> 0.05.…”
Section: Univariate Analysissupporting
confidence: 64%
“…The result of this study indicates that there is a significant relationship between the habit of washing hands and the level of skin hydration in the community in the Banyumas Regency area. The result of this study is supported by research conducted by Chairunnisa et al, (2020) which states that frequent exposure to soap and water can cause damage to the stratum corneum which can increase TEWL and decrease skin hydration-levels. 6, the result of the chi-square analysis shows that the p value between the habit of washing hands and the incidence of irritant contact dermatitis is 0.394> 0.05.…”
Section: Univariate Analysissupporting
confidence: 64%
“…Repeated and extended cleanser use can cause dry skin due to lipid erosion, increasing transepidermal water loss, losing its skin barrier function, and making it prone to irritation. 11 We found that 43 (11%) of 367 patients had food allergies. We found different results from the concept of risk factors for dermatitis.…”
Section: Discussionmentioning
confidence: 81%
“…Sebagai pemicu gatal, bahan iritan mampu mencetuskan dermatitis atopik. Sabun yang bersifat iritan adalah sabun dengan sifat alkalis, untuk itu pada pasien ini dianjurkan menggunakan sabun bayi karena memilik pH netral sehingga tidak iritatif (Chairunnisa et al, 2020). Kriteria terbanyak yang dimiliki oleh penderita adalah kriteria dengan kelompok dewasa dan jenis kelamin perempuan (Gunawan, 2022).…”
Section: Pembahasanunclassified